(untitled) (European Journal of Health Research, 2015)
The main objective is to identify and analyze falls that occur in people over 80 years old who belong to community. As a secondary aims are the correlation with autonomy and the definition of average TUG time. Retrospective epidemiological study of a cohort of over 80 years old, patient living alone in the community and/or a family of similar age, N=219 subjects. All episodes of falls were picked up and the times the event was repeated from 2009 to 2013. Of the total of 219 patients, 104 suffered 131 falls. 22.11% falls again and 3.80 presented more than three falls. The average incidence of falls per year is 14.03%. The average TUG time was 14.6 seconds ± 10.4, and for patients who suffered at least one fall was 18±11.5 seconds. The Pearson correlation of the TUG with the number of falls was positive (r=.25). The annual incidence is less than that in the bibliography. The results obtained in the TUG predictors have shown risk of falling, despite appearing false negative findings at 36.23%. The TUG cutoff point for our cohort corresponds to 10-12 seconds.